Industrial style Coffee table design from industrial wood waste - Noni Kusumaningrum (VISUAL, 2023)
In the wood processing industry, wood with A4 and A5 diameters is more in demand because of its quality but its existence is the rarest. One of the innovations in responding to the scarcity of high-quality wood within the scope of the furniture industry is the utilization of industrial waste in furniture design. This study aims to design a coffee table with an industrial style and know how to utilize industrial wood waste. Industrial style is one of the modern styles that is quite in demand. The character of this style appears simple, strong, mature, masculine, as it is, and does not require a lot of luxury and excess. The method used is the glassbox method or the method of thinking rationally and systematically. Starting from observation, analysis, synthesis, sketches, working drawings, and prototyping. The result is the utilization of industrial wood waste in the Finger Joint Laminated wood board (FJL) system in the design of the coffee table. The use of materials between iron and industrial wood waste FJL system on the Coffee table is able to handle the scarcity of wood and create a unique industrial style.